Survey and seasonal abundances of major insect pest species in the maize fields of Punjab, Pakistan - Naveed Akhtar; Hafiz Muhammad Tahir; Azizullah; Aamir Ali; Rabia Fajar; Ayesha Muzamil; Reham Fathy; Hend O. Mohamed; Dilawar Abbas (International Journal of Tropical Insect Science, 2025)

Cleaner and sustainable synthesis of high-quality monoglycerides by use of enzyme technologies: techno-economic and environmental study for monolaurin - Ahmad Mustafa; Sara Fathy; Ozben Kutlu; Fumiya Niikura; Abrar Inayat; Muhamad Mustafa; Tamer M. M. Abdellatief; Awais Bokhari; Olusegun David Samuel; Carlo Pastore; Luigi di Bitonto; M. A. Tawfik; et al. (Clean Technologies and Environmental Policy, 2023)
Currently, monoglycerides (MG) are produced using a complicated energy-intensive technology that contributes negatively toward greenhouse gas mitigation. This work suggests a cleaner and simpler one-step enzymatic production of α -monolaurin in an inert membrane reactor, where the reaction and enzyme separation are conducted simultaneously in one unit. Candida antarctica lipase (Lipozyme 435) was used to catalyze the esterification reaction between lauric acid and glycerin in a solvent-free system under mild temperatures. Response surface methodology was used to optimize the reaction conditions. The optimal conditions were a molecular sieve of 14.85% w/w, a temperature of 56.95 °C, an enzyme amount of 5.38% w/w, and a molar ratio of 4.75% w/w. The gas chromatography (GC) analysis showed that the α-monolaurin percentage was 49.5% when the enzymatic process (ENZ) was used. The conventional chemical (CHEM) and autocatalytic (AUT) esterification methods were also performed to study their proportional MG yields. The GC results showed the MG percentages of 43.9 and 41.7% for CHEM and AUT, respectively. Economic analysis was also conducted for the suggested enzymatic technique, and the findings were compared with those of the CHEM and AUT technologies. Using a plant capacity of 4950 t/year and 11% interest for the proposed ENZ process, the total capital investment of α-monolaurin production was preferably four times less than that of the CHEM process and three times less than that of the AUT method, presenting investment possibilities. However, the ENZ process showed the least profitability (net profit per day) among the three processes. Nevertheless, the return on investment and net present value for the ENZ process were preferably higher than those of CHEM and AUT because of its interestingly lower inside battery limit plant cost and less energy consumption. The AUT/CHEM processes generated a total carbon dioxide (CO 2 ) exhaust of 678.7 t CO 2 eq./year. In contrast, the ENZ process exhausted a total CO 2 of only 50 t CO 2 eq./year. The present integrated techno-economic and environmental study of α-monolaurin production emphasizes the green and cost benefits of the proposed ENZ technology. Graphical Abstract

Application of coliphage as biocontrol agent in combination with gamma irradiation to eliminate multi-drug-resistant E. coli in minimally processed vegetables - Salwa A. Abou El-Nour; Ali A. hammad; Reham Fathy; Amal S. Eid (Environmental Science and Pollution Research, 2023)
Biofilm formation is a rising concern in the food industry . Escherichia coli ( E. coli ) is one of the most important food-borne pathogens that can survive in food and food-related environments and eventually produce biofilms. This study suggested that both coliphages used were successful in preventing the creation of new biofilms as well as removing existing ones. Confocal laser scanning microscopy verified these findings. According to the findings, neither coliphage survived at 37 °C, but both remained stable at 4 °C and − 20 °C for extended periods of time. The study revealed that both coliphages demonstrated a greater degree of gamma irradiation resistance when compared to E. coli . The study’s results indicate that the implementation of a dual method, which incorporates gamma irradiation (1.5 kGy) and coliphage treatment, on various kinds of vegetables that were infected with E. coli , resulted in a significant reduction in bacterial count (surpassing 99.99%) following a 24-h incubation period. Combining gamma irradiation and the coliphage approach was significantly effective at lowering polysaccharide concentrations and proteins in the biofilm matrix. The results revealed that the pairing of gamma irradiation and coliphages acted in conjunction to cause disruptions in the matrix of biofilm, thereby promoting cell removal compared with either of the individual treatments. Ca + ions strengthen the weak virion interaction with the relevant bacterial host cell receptors during the adsorption process. In conclusion, use of coliphage in combination with gamma irradiation treatment can be applied to improve fresh produce’s microbial safety and enhance its storability in supermarkets. Graphical Abstract

Metabolic bioprofiling for discovering xanthine oxidase inhibitors from Glycyrrhiza glabra root solvent fractions using orthogonal separation modalities coupled with chemometry - Rahma SR. Mahrous; Hoda M. Fathy; Reham S. Ibrahim (South African Journal of Botany, 2023)

Strengthening the surface and adsorption properties of diatomite for removal of Cr(VI) and methylene blue dye - Nady A. Fathy; Sahar M. Mousa; Reham M. Aboelenin; Marwa A. Sherief; Alaa S. Abdelmoaty (Arabian Journal of Geosciences, 2022)
The main purpose of this work was to boost the surface and adsorption characteristics of diatomite (D) through chemical modifications with chitosan (DC), chitosan/titanium isopropoxide (DCTi), or chitosan/ graphene oxide (DCGr), respectively. Physicochemical characteristics of the prepared samples were investigated using SEM, TEM, XRD, FTIR, TGA, and porosity measurements. The impact of such modifiers into the D surface on the removal efficiency of chromium (VI) ions and methylene blue dye was studied in an equilibrium mode. Langmuir and Freundlich isotherms were used to analyze the adsorption data. Modifiers considerably enhanced the surface and textural properties of D through insertion of the main surface functional groups of chitosan and graphene oxide together compared to chitosan and titanium isopropoxide together or chitosan alone. In addition, the total surface area and total pore volume parameters of the unmodified D sample were improved greatly from 16.5 m 2 /g, 0.036 cm 3 /g to 39.8 m 2 /g and 0.174 cm 3 /g for DCGr, while they were 17.7 m 2 /g and 0.132 cm 3 /g for DC. The best adsorption results were well-defined with the Langmuir isotherm equilibrium model. Accordingly, the DCGr sample exhibited the highest uptake of Cr(VI) (about 167 mg/g) and methylene blue (66.7 mg/g). Hence, the chemical modification strategy of diatomite performed by using chitosan and graphene oxide significantly boosted the surface active sites and porosity properties and thus gave rise to the high adsorption capacity of Cr(VI) and methylene blue dye from wastewater. Hence, these findings affirmed the validity of the current strategy for surface modification of diatomite with chitosan and graphene oxide.

Enhancement of phenolic content, antioxidant and cytotoxic activities of Moringa oleifera leaf and seed by suspension culture - Reham Mustafa; E. M. B El-Naggar; Emil Svajdlenka; Gamal Omran; Fathy ELFiky; Amr El-Hawiet (Natural Product Research, 2021)

Impact of interleukin IL-6 rs-1474347 and IL-10 rs-1800896 genetic polymorphisms on the susceptibility of HCV-infected Egyptian patients to hepatocellular carcinoma - Reham M. Abd El-Baky; Helal F. Hetta; Gopala Koneru; Marwa Ammar; Engy A. Shafik; Dina A Mohareb; Muhammad Abbas El-Masry; Haidi K. Ramadan; Mohamed Zakaria Abu Rahma; Michael A. Fawzy; Moustafa Fathy (Immunologic Research, 2020)

Anticoagulant activity screening of an in-house database of natural compounds for discovering novel selective factor Xa inhibitors; a combined in silico and in vitro approach - Reham S. Ibrahim; Rahma SR. Mahrous; Hoda M. Fathy; Abdallah A. Omar; Rasha M. Abu EL-Khair (Medicinal Chemistry Research, 2020)